2012
DOI: 10.3928/01477447-20121023-13
|View full text |Cite
|
Sign up to set email alerts
|

Changing Transfusion Practice in Total Hip Arthroplasty: Observational Study of the Reduction of Blood Use Over 6 Years

Abstract: Patients undergoing primary total hip arthroplasty (THA) have historically been over-transfused. In a district general hospital setting, the authors observed a significant downward trend in blood transfusion requirements in these patients over 6 years after a change in transfusion policy. The purpose of this study was to retrospectively analyze the change in transfusion practice and present the results of the restrictive transfusion policy. All patients undergoing primary THA between January 2003 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Borghi et al reported allogeneic RBC transfusion requirements of only 10% for total hip and knee arthroplasty patients [ 24 ]. However, that study and other studies reporting low transfusion rates have been focused studies, investigating the use of a new transfusion protocol [ 25 , 26 ] or the use of autologous transfusion programs [ 27 ]. It is difficult to compare studies since, besides differences in study design and study populations, some investigators only included postoperative transfusions but not intraoperative ones in their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Borghi et al reported allogeneic RBC transfusion requirements of only 10% for total hip and knee arthroplasty patients [ 24 ]. However, that study and other studies reporting low transfusion rates have been focused studies, investigating the use of a new transfusion protocol [ 25 , 26 ] or the use of autologous transfusion programs [ 27 ]. It is difficult to compare studies since, besides differences in study design and study populations, some investigators only included postoperative transfusions but not intraoperative ones in their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, THA and TKA are the leading indications for blood transfusion in surgical patients, and blood transfusion is an independent predictor of increased postoperative mortality, especially for patients with preoperative anemia and comorbidities (). Because initiatives to reduce the frequency of perioperative blood transfusion are being taken worldwide, decreasing utilization of blood transfusion in patients undergoing THA and TKA has recently been noted (). Thus, we cannot exclude the possibility that changes in transfusion practice in THA or TKA over the last 2 decades have confounded interpretation of Lalmohamed and colleagues' results.…”
mentioning
confidence: 99%